Les - ekološko gradivo - Zbašnik-Senegačnik, Martina (Les (Ljubljana), 1998)
In general, materials which have been used in construction, have had a negative influence in all the phases of the life cycle. The effects can be seen in the form of tampering with the environment, overuse of electric power, harmful emissions and wastes in the form of pollution with vapors, dust, fibers, poisonous and radioactive matter. The wood is natural and kind material which does not have any side effects to the environment and mankind. Wrong surface finishing and certain wood semi products contain harmful emissions which pollute nature and has bad influences to the health of mankind. But correct use makes the wood very ecological and user friendly material.
Keywords: gradiva; les; natural environment; okolje; ecology; ekologija